2004
DOI: 10.1111/j.1365-2486.2004.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide and methane fluxes from soils of the Orinoco savanna under different land uses

Abstract: The study investigates the effect of land-use change on nitrous oxide (N 2 O) and methane (CH 4 ) fluxes from soil, in savanna ecosystems of the Orinoco region (Venezuela). Gas fluxes were measured by closed static chambers, in the wet and dry season, in representative systems of land management of the region: a cultivated pasture, an herbaceous savanna, a tree savanna and a woodland (control site). Higher N 2 O emissions were observed in the cultivated pasture and in the herbaceous savanna compared with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 56 publications
(93 reference statements)
3
10
0
1
Order By: Relevance
“…As in our study (Table 4), Rees et al (2006) also reported a strong positive correlation between N 2 O fluxes and soil moisture. The lower emissions in our study are thus most likely related to dryer soil conditions: 23% WFPS in our study vs. 60% WFPS observed by Castaldi et al (2004) and 75% WFPS observed by Br€ ummer et al (2008). As previously shown for tropical forest ecosystems , we also found that N 2 O emissions positively correlated with total soil nitrogen contents (N tot ) and…”
Section: In Situ Concentrations Of N and C In Soil Watersupporting
confidence: 83%
See 1 more Smart Citation
“…As in our study (Table 4), Rees et al (2006) also reported a strong positive correlation between N 2 O fluxes and soil moisture. The lower emissions in our study are thus most likely related to dryer soil conditions: 23% WFPS in our study vs. 60% WFPS observed by Castaldi et al (2004) and 75% WFPS observed by Br€ ummer et al (2008). As previously shown for tropical forest ecosystems , we also found that N 2 O emissions positively correlated with total soil nitrogen contents (N tot ) and…”
Section: In Situ Concentrations Of N and C In Soil Watersupporting
confidence: 83%
“…DOC concentrations were highest at 10 cm soil depth, with significantly higher values in homegarden (median: 4.7 mg C L À1 ) and forest ecosystems (median: 1.5-14.5 mg C L À1 ) than in the coffee plantation (median: 2.5 mg C L À1 ). for herbaceous and open tree savanna in Venezuela (Castaldi et al, 2004); 0.25-0.52 kg N ha À1 year À1 for grass and woodland savanna in Zimbabwe (Rees, Wuta, Furley, & Li, 2006); and 0.52-0.67 kg N ha À1 year À1 for shrub and woodland savanna in Burkina Faso (Br€ ummer et al, 2008). As in our study (Table 4), Rees et al (2006) also reported a strong positive correlation between N 2 O fluxes and soil moisture.…”
Section: In Situ Concentrations Of N and C In Soil Watersupporting
confidence: 80%
“…Soil WFPS at all sites was always below 60.0% except during freeze-thaw cycle and immediately after heavy rainfall. The coarse texture and the low water retention capacity of soils limited the possibility of the formation of anaerobic microsites, where N 2 O production could take place (Castaldi et al 2004). Nitrous oxide emission is affected by soil moisture (Ciarlo et al 2008), and indeed higher N 2 O emission occurred after raining in this study.…”
Section: Discussionmentioning
confidence: 54%
“…O metano também não foi considerado para os cál-culos, porque estudos (Simona et al, 2004;Six et al, 2004;Metay et al, 2007) têm mostrado que seus fluxos não são significativos (-0,01 ± 0,07 mg CH 4 m -2 d -1 ) em áreas agrícolas, sendo as maiores emissões encontradas no cultivo de arroz irrigado por inundação (Agostinetto et al, 2002). Além disso, a fertilização nitrogenada aumenta a emissão de N 2 O do solo para a atmosfera, como também diminui a absorção de CH 4 atmosférico pelos solos (Mosier et al, 1991).…”
Section: O Sequestro De C No Solounclassified